1989
DOI: 10.1128/mcb.9.6.2289
|View full text |Cite
|
Sign up to set email alerts
|

GPA1Val-50 mutation in the mating-factor signaling pathway in Saccharomyces cerevisiae.

Abstract: The GPAI gene of Saccharomyces cerevisiae encodes a protein that is highly homologous to the a subunit of mammalian hetrotrimeric G proteins and is essential for haploid cell growth. A mutation of the GPA1 protein, GPA1Val-50, in which Gly-50 was replaced by valine, could complement the growth defect of a GPAI disruption, gpal::HIS3. However, cells with gpal ::HIS3 expressing the GPAlVaI-S5 protein were supersensitive to a-factor in a short-term incubation but resumed growth after long-term incubation even aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
66
2

Year Published

1990
1990
2000
2000

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(73 citation statements)
references
References 34 publications
5
66
2
Order By: Relevance
“…4), as was also observed by others for mutations at this amino acid [Miyajima et al 1989;Stone and Reed 1990}. The a-factor spot results in a small area of growth inhibition of wild-type cells and a large, clear zone of growth arrest of an sst2 mutant, which is defective in desensitization to phero- (Chan and Otte 1982;Dietzel and Kurjan 1987b).…”
Section: Glycine To Valine Substitution Results In Multiple Effectsmentioning
confidence: 58%
See 2 more Smart Citations
“…4), as was also observed by others for mutations at this amino acid [Miyajima et al 1989;Stone and Reed 1990}. The a-factor spot results in a small area of growth inhibition of wild-type cells and a large, clear zone of growth arrest of an sst2 mutant, which is defective in desensitization to phero- (Chan and Otte 1982;Dietzel and Kurjan 1987b).…”
Section: Glycine To Valine Substitution Results In Multiple Effectsmentioning
confidence: 58%
“…11. This mutant showed multiple phenotypes, some of which differ from results of Miyajima et al (1989; see Discussionl. The a scgl :: LEU2 [pTRP1-MATa YEp352-scgl w15°] strain could lose pTRP1-MATa (Table 1); the resulting strain showed normal growth but was sterile.…”
Section: Glycine To Valine Substitution Results In Multiple Effectsmentioning
confidence: 83%
See 1 more Smart Citation
“…The pheromone response pathway is exquisitely sensitive to changes in Gpa1p expression (Cole et al, 1990;Kang et al, 1990). Studies of other GPA1 mutations have revealed different phenotypes when expressed on a centromere-based plasmid instead of the chromosomal locus (Miyajima et al, 1989;Kurjan et al, 1991). We found that haploid cells expressing the mutant allele as the sole copy of GPA1 were viable.…”
Section: Gpa1p Is Dually Myristoylatedmentioning
confidence: 70%
“…Other genetic observations suggested a direct interaction between SST2 and GPA1. First, certain mutations in the G␣ gene could bypass the requirement for a fully active SST2 gene (30,31). Second, the recovery-promoting effect of G␣ overexpression was more efficient if residual SST2 function was present (32,33).…”
Section: Establishing a Paradigm: Identification Of Yeast Sst2mentioning
confidence: 99%